Plenary Collaboration #1: Citation, Appropriation, and Abolition - Sandler, Matt; Sinanan, Kerry; Zuroski, Eugenia (Romanticism on the Net)

(untitled) (Université de Montréal, 2024)
Because part of the project of the "Black Studies and Romanticism" virtual conference was to shake up the structures and systems of regular conferences, we attempted to instigate “plenary collaborations,” giving two groups of scholars a space for a plenary, on a pre-meditated topic or set of questions, which might take shape in whatever way they together saw fit—whether a conversation, a scripted exchange, or something more creative. We were hoping that adjusting the format would better suit the virtual medium and likewise give everyone a break from the individualist, Romantic genius shape of usual plenaries. While each plenary gave extended time for individual responses, there were many touchbacks and nexus points, both during talks and during Q&A recorded at their ends.The first group of plenarists wanted to think about the colonial and decolonial means of knowledge exchange among Romanticism and other fields, in particular between Romantic-era writers and scholars and Black writers and scholars, which necessarily included some transformational practices for Romantic-era thinking and writing. To begin, Kerry Sinanan suggests, through the purview of womb theory, that Black Studies does not need Romanticism, but Romanticism needs Black Studies to think foundationally about the enslaved lives have built the material realities and ideals of liberation, freedom, and abolition. Matt Sandler redresses the early twentieth-century Black women scholars who had already been studying the period, then continues to explore how and why nineteenth-century Black authors made European Romanticism open to thinking about Blackness. Eugenia Zuroski, finally, contemplates alternative citational practices learned from Black and Indigenous folx as a mode of site-tation, which rejects notional counting and instead reorients knowledge as shaped by places, affects, and relations.